Regulation of mitochondrial dynamics in cardiomyocytes: implications for cardiac health and disease - Zhang, Tengxu; Li, Ziwei; Xu, Ying; Xu, Chaoqun; Wang, Hao; Rui, Tao (Frontiers in Cell and Developmental Biology, 2025)
Mitochondrial dynamics, involving fission and fusion, are vital for maintaining mitochondrial quality, shape, and function in heart cells. This review explores how key regulators—Dynamin-related protein 1 (Drp1), mitofusins 1 and 2 (Mfn1/2), and Optic Atrophy 1 (OPA1)—control these processes in the heart. Drp1 facilitates fission, while Mfn1/2 and OPA1 mediate outer and inner membrane fusion. Their activities are finely tuned by modifications, gene regulation, and stress pathways. Disruptions in these dynamics can impair functions like energy production, calcium balance, ROS management, and mitophagy, contributing to heart diseases. Abnormal fission and fusion are also linked to conditions such as sepsis, ischemia/reperfusion injury, and diabetic cardiomyopathy. This review aims to offer a thorough analysis of recent advancements in the understanding of dysregulated mitochondrial dynamics and their contribution to cardiac pathology. Additionally, it evaluates emerging therapeutic strategies that target the balance between mitochondrial division and fusion. We posit that precise modulation of the activities of Drp1, Mfn1/2, and OPA1 presents significant potential for the treatment of cardiac diseases. However, achieving tissue specificity and temporal control remains a critical challenge for clinical translation.